Moisture Content of Dried (Eucheuma Cottonii) Seaweed In Nunukan Regency - fendi fendi; Abdul Rohman Nasrudin; Novera Novera; Nur Nadia (Jurnal Sains dan Teknologi Perikanan, 2026)
Nunukan Regency is one of the major production centers of Eucheuma cottonii seaweed in North Kalimantan, playing an important role as a supplier of raw materials for carrageenan production and as a contributor to the regional economy. Dried seaweed is the primary traded commodity; however, its quality is highly influenced by moisture content, as this parameter affects market value, susceptibility to fungal growth, and product shelf life. According to the Indonesian National Standard (SNI 2690:2015), the maximum allowable moisture content for dried seaweed is 35%. The traditional sun-drying practices that are still commonly used in Nunukan may result in uneven moisture levels due to fluctuating weather conditions.This study aims to analyze and compare the moisture content of dried Eucheuma cottonii obtained from various cultivation sites in Nunukan Regency and to evaluate its compliance with SNI 2690:2015. The results of this study are expected to provide essential information for farmers and industry stakeholders in improving the quality of dried seaweed products in order to meet domestic and international market standards.